Postoperative Neutrophil to Lymphocyte and Platelet Ratio and Delayed Graft Function - Oliveira,João (2023)
ABSTRACT Introduction: Delayed graft function (DGF), an outcome for which inflammation is critical, has been associated with worse outcomes after kidney transplantation (KT). The neutrophil to lymphocyte and platelet (NLP) ratio is a biomarker of systemic inflammation. We assessed postoperative NLP ratio applicability as an early predictor of DGF in KT patients. Methods: Retrospective cohort of adult patients submitted to KT at our unit, between 1 January 2010 and 31 December 2020. NLP was calculated at 24 hours post-KT. Primary outcome was development of DGF. Logistic regression was calculated to determine significant factos which may have contributed to DGF. Results: We included 527 patients with a mean age of 49.9 ± 12.8 years. In 47.8% of patients expanded criteria donors were used, and in 3.6% non-heart-beating donors. DGF occurred in 17.8% of patients. Mean post-KT NLP was higher in patients submitted to induction therapy with lymphocyte depleting antibodies (50.2±40.3 vs 11.9±7.4 with basiliximab, p<0.001), but it was found to be higher even before KT (5.2±1.8 vs 1.9±1.2, p=0.001). Grafts from non-heart-beating donors (OR 13.989, 95% CI 4.741, 41.274, p=0.000), longer warm ischemia time (OR 1.035, 95% CI 1.007, 1.064, p=0.014) and higher NLP ratio 24 hours after transplantation (OR 1.009, 95% CI 1.002, 1.016, p=0.015) were independently associated with DGF. Conclusion: Higher NLP ratio at 24 hours after KT was independently associated with DGF. This reflects the impact of inflammation on KT outcomes and highlights the role of the NLP ratio as a sensitive marker of systemic inflammatory response after KT.